THE PORTRAIT OF INSPIRING ENGLISH LECTURERS IN ENGLISH DEPARTMENT, FACULTY OF LANGUAGES AND LITERATURE, STATE UNIVERSITY OF MAKASSAR BASED ON STUDENTS PERCEPTION - Nurqalbi, Nurqalbi; Samtidar, Samtidar; Sakkir, Geminastiti (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
This research aims to determine students perception of inspiring English lecturers and portrait of  inspiring  English  lecturers  in  English  Department,  Faculty  of  Languages  and  Literature, State University of Makassar. The researcher applies mixed-methods research to achieve the research objectives. The data was collected in the form of a Likert questionnaire and interviews. The  subjects  of  this  study  were  students  in  the  2019  English  Language  Education  Study Program. The sample questionnaire had 35 students, and the interviews were with 5 students who  were  taken  using  a  voluntary  sampling  technique.  Data  analysis  findings  revealed  that students'  perceptions  of  portraits  inspiring  English  lecturer  with  a  classification.  20%  of students were classified as very positive, and 80% of students were classified as positive, and no students had moderate, negative, or very negative perceptions. (2) Based on the data from students  interviews,  an  inspiring  English  lecturer  is  one  who  provides  motivation,  feedback, appreciates students, punctuality, cares, has English language skills, good teaching strategies, firm and disciplined. Therefore, it can be concluded that students think that the English lecturer in the English department is an inspiring English lecturer. Keywords— Inspiring English Lecturers, Students’ Perception